PENGENDALIAN BIAYA PROYEK KONSTRUKSI DENGAN KONSEP EARN VALUE ANALYSIS - Mulyati, Ely; Nurhasanah, Nurhasanah (Universitas Bina Taruna Gorontalo, 2024)
Earned Value Analysis (EVA) is a powerful and effective tool in construction project cost and schedule control. With proper implementation, EVA can help project managers to keep the project within the set budget and schedule, and increase the chances of overall project success. Although it faces challenges in its implementation, the benefits derived from using EVA far outweigh them, making it an invaluable approach in construction project management. Based on the BCWP value and the percentage of work realization obtained from the calculation until week 33 is Rp.6,601,973,900, - less than the BCWS value until week 33, which is Rp.7,686,078,000, - with a difference in realized and planned costs of Rp.1,084,104,100 and Rp.1,084,104,100. .084,104,100 and the percent progress realization of 68.699% is less than the percent plan which is 79.98%, with a difference in percent realization and plan of 11.28% this shows that until week 33 the project is delayed by 3 weeks from the scheduled plan. By using the BCWP value and the CPI value, the estimated value of the remaining cost or ETC is Rp.2,758,926,605, - and the estimated final cost of the project or EAC is Rp.8,609,028,353, 48 the EAC value is smaller than the planned budget cost of Rp.9,610,000,000, - meaning that the Earned Value to be obtained by the company is Rp.1,000,971,647